Morphometric and molecular characterization of an expanding Ionian population of the fireworm Hermodice carunculata (Annelida). (31st July 2019) - Righi, Sara; Maletti, Isabella; Maltagliati, Ferruccio; Castelli, Alberto; Barbieri, Michele; Fai, Sergio; Prevedelli, Daniela; Simonini, Roberto
Abstract: The amphinomid fireworm Hermodice carunculata is a potentially invasive species reported throughout the subtropical Atlantic Ocean and the Mediterranean Sea, which is known as a generalist predator and opportunistic feeder. The ongoing climate changes and seawater warming may favour fireworm poleward range expansions and density increases. Our results provide the first investigation into a population which has purportedly been spreading widely in the Salento Peninsula (Apulia, Italy). The specimens were analysed using allometric variables and molecular markers. The best morphometric parameters to estimate individual size were determined as key information for future studies on fireworm population dynamics. To phylogeographically characterize the Apulian population, sequences of the mitochondrial COI and 16S rDNA regions were obtained from a pool of individuals and treated together with those of Atlantic specimens retrieved from GenBank. The estimates of genetic variability for Apulian population were consistent with those recently reported in the literature. Inferences on demographic history analysis confirmed a recent expansion event in Apulia, as has been recounted by fishermen and scuba divers during recent years. Overall, these results constitute a crucial step in the characterization of present-day H. carunculata populations, and provide greater insight into fireworm population ecology.